Zingiber Officinale Water Extract Effect on Sperm of Alloxan-Induced Diabetic Mice: an In Vitro Examination of Sperm DNA Fragmentation, Fertilization and Embryonic Development Outcomes - Hussein, Zena M (Al-Nahrain Journal of Science, 2018)
Diabetes mellitus (DM) represents one of the common threats to modern global health. There are several factors increasingly encourage the occurrence of this disease for example obesity, population growth and ageing. The DM may affect male fertility at different level of functionality, by affecting on endocrine hormones that regulate spermatogenesis or affecting on spermatogenesis itself, impairing penile erection and ejaculation, reducing testosterone, increasing percentage of sperm DNA fragmentation. In fact, high level of sperm DNA fragmentation may lower natural conception, intrauterine insemination (IUI), and in vitro fertilisation (IVF) outcomes. The aim of this study was to investigate the potential therapeutic effect of water extract of Zingiber officinale (Z. officinale) roots in alloxan-induced diabetic mice on improving sperm quality and fertilization rate and early embryonic development outcomes. Male mice have subjugated for alloxan injection to induce diabetes mellitus. Diabetic males were treated with Z. officinale extract for 35 days at 50 and 100 mg/kg body weight bw. Data showed a significant enhancement in sperm parameters (count, motility and abnormal morphology), reduction of sperm DNA fragmentation rates, IVF outcomes and early embryonic development rates. In conclusion, the study suggests that Z. officinale possess a potential therapeutic effect to improve diabetic male with fertility problems.